Empagliflozin adjunct with metformin for the inhibition of hepatocellular carcinoma progression: Emerging approach for new application - Amir Mohamed Abdelhamid (Elsevier, 2022)
Hepatocellular carcinoma (HCC) is on the rise worldwide, and its incidence in diabetic patients is two to three times that of non-diabetics. Current therapeutic options fail to provide considerable survival benefits to patients with HCC. There is a strong possibility that the FDA-approved antidiabetic combination of empagliflozin and metformin could show complementary effects to control HCC progression. However, their multitarget effects have not yet been studied on HCC development. Therefore, the present study aims to evaluate the antitumorigenic activity of this combination in non-diabetic mice with diethylnitrosamine-induced HCC. Empagliflozin/metformin combination prolonged survival and improved histological features of mice livers. Additionally, Empagliflozin/metformin showed anti-inflammatory potential and relieved oxidative stress. On the one hand these effects are likely attributed to the ability of metformin to inactivate NF-κB in an AMPK-dependent mechanism and on the other hand to the ability of the empagliflozin to inhibit the MAPKs, p38 and ERK1/2. Empagliflozin also showed a less robust effect on AMPK than that of metformin. Moreover, empagliflozin enhanced the autophagy inducing activity of metformin. Furthermore, empagliflozin/metformin exhibited increased apoptotic potential. Consequently, empagliflozin augmented the antitumorigenic function of metformin by exerting better control of angiogenesis, and metastasis. To conclude, our findings suggest empagliflozin as an ideal adjunct to metformin for the inhibition of HCC progression. In addition, since the incidence of hypoglycemia is minimal due to insulin-independent mechanism of action of both treatments, empagliflozin/metformin could be a promising therapeutic modality for the management of diabetic patients with HCC; and even non diabetic ones.